An investigation into the neuroprotective effects of dehydroepiandrosterone - Palvie, Stefanie Michelle (Rhodes University, Faculty of Pharmacy, Pharmacy, 2006)
Dehydroepiandrosterone, a C-19 steroid, is found endogenously with the highest circulating serum levels. It is converted to important steroids such as the sex hormones oestrogen and testosterone. DHEA has come under the spotlight as a purported "fountain of youth" due to its well-characterised age-related decline. The supplementation of DHEA in both the elderly and those with a pathophysiological deficiency has been shown to be of benefit, particularly with regard to wellbeing and depression. The role of DHEA in the periphery has not been elucidated beyond its role as a precursor hormone in sex steroid biosynthesis, though it has been established as a neuroactive neurosteroid, capable of exerting neuroprotective effects in the brain. Since the importance of free radicals in aging and neurodegeneration is well established, investigations were conducted on the ability of DHEA to inhibit free radical generation or scavenge existing free radicals. DHEA was able to significantly inhibit quinolinic acid-induced lipid peroxidation, a measure of membrane damage, over a range of concentrations, although the reduction did not appear to be dose-dependent. This was observed in both in vitro and in vivo studies. Thus, the ability of a compound to reduce the degree of lipid peroxidation may indicate its value as a neuroprotectant. However, DHEA did not significantly reduce cyanide induced generation of the superoxide free radical, suggesting that DHEA is not an effective free radical scavenger of the superoxide anion and that the reduction in lipid peroxidation does not occur through a scavenging mechanism. Apoptosis is a physiological process which is necessary for development and homeostasis. However, this form of programmed cell death can be initiated through various mechanisms and too much apoptotic cell death results in deleterious effects in the body. DHEA was shown not to induce apoptosis. Even the lowest concentration of DHEA investigated in this thesis shows a remarkable decrease in the degree of apoptosis caused by intrahippocampal chemical insult by the neurotoxin quinolinic acid. Cresyl violet was used to visualise tissue for histological examination which revealed that DHEA is able to preserve the normal healthy morphology of hippocampal cells which have been exposed to quinolinic acid. Cells maintained their integrity and showed little evidence of swelling associated with necrosis. Organ culture studies were performed by assessing the impact of DHEA on several pineal metabolites. The study revealed that DHEA exerted an effect on the metabolism of indoleamines in the pineal gland. Melatonin, the chief pineal hormone, did not appear to be affected while the concentrations of N-acetylserotonin, serotonin and methoxytryptamine showed significant alterations. Thus, the neuroprotective mechanism of DHEA does not appear to be mediated by an increase in the presence of melatonin. The biological importance of metal ions in neurodegeneration is also well established and thus the potential interaction between DHEA and metal ions was considered as a mechanism of action. Spectroscopic and electrochemical analyses were performed to determine whether DHEA is able to interact with metal ions as a ligand. These reveal that DHEA does not form a strong bond with the metals investigated, namely copper (II) and iron (III), but that a weak interaction is evident. These investigations were conducted in a rodent model, which has neither large amounts of endogenous DHEA, nor the enzymatic infrastructure present in humans. Thus, the theory that DHEA exerts its effects through downstream metabolic products is unlikely. However, these investigations reveal that there is merit in the statement that DHEA itself is a neuroprotective molecule, and confirm that the further investigation of DHEA is an advisable strategy in the war against neurodegeneration and aging.
Keywords: Aging -- Physiological aspects; Nervous system -- Degeneration -- Treatment; Steroid hormones; Dehydroepiandrosterone; Dehydroepiandrosterone -- Therapeutic use; Neurosciences; Neuroanatomy; Apoptosis; Pineal gland -- Physiology; Neurotoxic agents; Free radicals (Chemistry) -- Physiological effect